Strategic ESG Integration as a Mediating Mechanism between Board Governance and Financial Performance - Apriwati Br Barus; Syahrial Sitorus (Cattleya Darmaya Fortuna, 2026)
This study examines how board governance influences strategic Environmental, Social, and Governance (ESG) integration and its implications for corporate financial performance among companies listed on the Indonesia Stock Exchange. Unlike previous studies that primarily focus on ESG disclosure, this research emphasizes substantive ESG integration into corporate strategy through a newly developed Strategic ESG Integration Index (ESG-SI). The study employs a quantitative explanatory approach using balanced panel data covering the 2019–2025 period. Board governance is measured through both structural and process dimensions, including board independence, gender diversity, ESG expertise, sustainability committee, ESG agenda intensity, and ESG-linked executive incentives. Panel regression with firm and year fixed effects is used to examine direct relationships, while mediation analysis is performed using bootstrapping techniques and robustness tests with alternative performance measures. The findings indicate that board ESG expertise, the intensity of ESG discussions, and ESG-linked executive incentives significantly enhance strategic ESG integration. Furthermore, ESG-SI positively affects Return on Assets (ROA) while reducing the Cost of Equity (COE), with stronger effects observed in industries characterized by higher ESG risk. The results confirm that strategic ESG integration mediates the relationship between effective board governance and corporate financial performance. This study contributes to the literature by distinguishing strategic ESG integration from symbolic ESG disclosure through an auditable process-based measurement framework. The findings provide practical implications for strengthening board ESG capabilities, institutionalizing sustainability governance, and aligning executive incentives with long-term sustainability objectives in emerging markets.